Aspectos biológicos do nematoide do cisto das cactáceas, Cactodera cacti, em pitaia - Café, Francisco Bruno da Silva (2019)
Heteroderids stand out in world agriculture for crop damage and long soil survival through structures called cysts. In Ceará, the cactaceous cyst nematode, Cactodera cacti, is the only phytonematode of the Heteroderidae family present. This pathogen was registered in the state in 2016 naturally occurring in mandacaru, Cereus jamacaru. Considering that C. cacti affects economically exploited cactus in several countries and considering the threat of this nematode to the state of Ceará where there is commercial cultivation of cactus, this study aimed to: 1) study the life cycle of C. cacti in red pitahaya, Hylocereus sp.; 2) to evaluate the multiplication capacity of C. cacti by counting second stage eggs and juveniles (J2) in 70 cysts; 3) determine the time for formation and hatching of juveniles in vitro; 4) evaluate the viability of 50 cysts in dry soil without host for 30, 60, 90, 120, 150 and 180 days and for 26 months; 5) investigate your hosts. In the life cycle study of C. cacti in red pitahaya it was observed that females with eggs suck at 18 days and cysts at 24 days after inoculation. In determining the multiplication capacity of C. cacti in red pitahaya, it was found that the number of eggs and J2 per cyst ranged from 91 to 232, with cysts containing a range of 100 to 150 individuals being more common. In the definition of the time for formation and hatching of juveniles in vitro, it was observed that the emergence of first and second stage juveniles occurred with four and eight days, respectively, and that the hatching occurred at 11 days of evaluation. Investigating the survival of cysts at intervals of 30 to 180 days, it was found that 2,033 to 2,496 cysts were formed in pitahaya roots grown for 45 days in pots of each treatment. The time of 26 months did not affect the viability of the cysts, and it was possible to observe more than 1,300 cysts and females in roots after 45 days of planting pitahaya. In the investigation of host plants, in inoculations with 2,000 C. cacti eggs in plant species of families Apiaceae, Cactaceae, Crassulaceae, Euphorbiaceae, Lamiaceae and Solanaceae, evaluated after 45 days, it was found that only plant species of Cactaceae family were infected by C. cacti, presenting a reproduction factor of 2.3 to 13.98. It was observed that, particularly in red pitahaya, the pathogen greatly increases its population and in a short time.